Micromesh Fabric Pollination Bags for Switchgrass. Issue 4 (1st July 2014) - Vogel, K. P.; Sarath, G.; Mitchell, R. B.
ABSTRACT: Pollination bags for making controlled crosses between switchgrass ( Panicum virgatum L.) plants were made from a polyester micromesh fabric with a mesh size of 41 µm, which is smaller than the mean reported 43 µm diameter of switchgrass pollen. When used in paired‐plant crosses between switchgrass plants, the mean amount of seed produced per plant was about 1 g, or approximately 800 seeds, which was significantly greater than the 10 to 250 seeds produced previously in paired‐plant crosses of switchgrass using paper pollination bags. The four‐ to tenfold increase in seed produced per cross enables the progeny of the crosses to be evaluated in larger numbers in genetic studies and in replicated space‐transplanted or seeded sward evaluation trials. The micromesh pollination bags cost about 15 each because of fabric costs but could be reused for 10 or more pollination seasons at an annual cost per cross of about 1.50 or less.